2010
DOI: 10.1074/jbc.m110.156240
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Docking Site for DNA Polymerase α-Primase on the SV40 Helicase Is Required for Viral Primosome Activity, but Helicase Activity Is Dispensable

Abstract: Replication of simian virus 40 (SV40) DNA, a model for eukaryotic chromosomal replication, can be reconstituted in vitro using the viral helicase (large tumor antigen, or Tag) and purified human proteins. Tag interacts physically with two cellular proteins, replication protein A and DNA polymerase ␣-primase (pol-prim), constituting the viral primosome. Like the well characterized primosomes of phages T7 and T4, this trio of proteins coordinates parental DNA unwinding with primer synthesis to initiate the leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 74 publications
2
22
0
Order By: Relevance
“…LTag unwinds the origin DNA, recruits RPA to the template, and then orchestrates RPA displacement by human Pol-prim for primer synthesis and extension. In a simpler reaction utilizing RPA-coated ssDNA as the template, LTag and Pol-prim are sufficient to reconstitute SV40 primosome activity even in the absence of LTag helicase activity (27)(28)(29)(30). These findings suggested that the key role of LTag in primosome activity may be to displace RPA and, in concert, position Pol-prim on the exposed ssDNA.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…LTag unwinds the origin DNA, recruits RPA to the template, and then orchestrates RPA displacement by human Pol-prim for primer synthesis and extension. In a simpler reaction utilizing RPA-coated ssDNA as the template, LTag and Pol-prim are sufficient to reconstitute SV40 primosome activity even in the absence of LTag helicase activity (27)(28)(29)(30). These findings suggested that the key role of LTag in primosome activity may be to displace RPA and, in concert, position Pol-prim on the exposed ssDNA.…”
mentioning
confidence: 73%
“…The interface on LTag consists of a hydrophobic patch centered on Tyr-552, Phe-617, and Met-621, flanked on one edge by a few positively charged residues. The LTag residue that had previously been implicated in p68N binding, Lys-425 (27), is not part of this interface (Fig. 3B and supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its structure is not known, although the structure of the heterodimeric yeast pol alpha has been determined (Klinge, Nunez-Ramirez et al 2009). The human enzyme has been shown to bind T antigen (Dornreiter, Hoss et al 1990;Collins and Kelly 1991;Collins, Russo et al 1993;Dornreiter, Copeland et al 1993) and this interaction is needed for DNA replication (Taneja, Boche et al 2007); (Huang, Zhao et al 2010). Given its size, it might very well cover a substantial part of a hexamer.…”
Section: Association Of Rpa With the Initiation Complexmentioning
confidence: 99%